PEMAKNAAN HUMANISME PANCASILA DALAM RANGKA PENGUATAN KARAKTER BANGSA MENGHADAPI GLOBALISASI - Subekti, Slamet (HUMANIKA, 2013)
ABSTRACT Today Indonesia is facing the challenges of globalization, especially in its cultural dimension has brought the threat to the continuity of national culture. Historically Pancasila ideology has been an integrating force is quite steady as a common platform for the nation-state of Indonesia. The existence of Pancasila should be shown again as a public discourse that is open to interpretation in accordance with the demands of the contemporary with the times. Therefore, the meaning of Pancasila humanism necessary in order to strengthen the nation's character in order to face the challenges of globalization. Keywords: Pancasila, humanism, Nation’s character, Globalization